Hantering och lastning av nöt på gården : praktiska studier vid hämtning av slaktdjur - råd för att minska stress och skador på djur och människor - Ekman, Lars (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2003)
There is present a lot of focus on animal welfare issues during transport and the related loading and unloading of animals. This thesis is a field study investigating the present situation of beef and dairy farms in Sweden. The predominant reasons stressing cattle when transported to abattoirs are when they are loaded and unloaded on the trucks. The aim of this thesis is to improve the handling and the loading facilities to facilitate the handling and reduce the stress for the animals as well as the personnel. The field study was done by travelling together with the transports from the farm to the abattoir in Uppsala. Three trucks where used and about 60 farms were visited January to March 2003. The loading of 220 cattle were registered. Following were registered at each farm; loose or tied up cattle, floor, type and amount of litter on the alley floors, gates and other aid to direct the animals, noise and light conditions the angle of the loading ramp, material in ramp, and animal behaviour, especially slipping. The absolutely main reason why cattle balk is the appearance of the floor in the alleys. Very few farms used litter in the alleys where the animals should walk to the loading ramp. Many cattle slipped or balked on the floors who where too slippery or appeared uncommonly. Another main reason why the cattle stopped or balked if been tied up was that the animal was forced to jump over the dung channel and then slipped when landing on the other side. All animals from farms with tied up dairy cows were loaded directly from the ground outside the building without anything to reduce the angle of the loading ramp to the truck. All farms with specialised beef production held their animals loose in pens with slatted floor or deep bedding. However only 25 % of those farms had specially loading facility. Cattle walk towards lighter illuminated areas, they don't want to go into dark areas. The light conditions in the buildings and the truck can be used to make the loading easier. The truck and the alleys to the truck should be brighter illuminated than the box. In that way the cattle always walk towards brighter illuminated areas. Conclusions and recommendations: The angle of the loading ramp or loading stairs should not exceed 20 degrees and not 0 degrees. Reducing the loading angle closer to 0 than 20 degrees will make the loading easier. An easy way to prevent the cattle from jumping over the dung channel would be to bridge over the dung channel and then hide the bridge by litter. All alleys should be littered one or two days before the transport of the cattle. The litter then will be a little bit wet and get stuck to the floor and in that way give the cattle a good grip.